Co-offending and police notification: the differential reporting of young groups to the police - Lantz, Brendan (Psychology, crime & law, 2024)
Despite a wealth of research on the decision to notify police following victimization, there has been relative inattention to the role of a basic feature of crime: the tendency for individuals to offend in groups. Following this, the current research examines the influence of co-offending on the decision to notify police using information from the National Crime Victimization Survey. Results indicate that the co-offending is significantly and positively related to the likelihood of notification. Findings further indicate that this relationship is moderated by co-offender characteristics, such that young co-offenders and, to a lesser extent, male co-offenders are more likely than their counterparts to be reported to police. These results have important implications for understanding the invocation of both formal social control and disparities in these processes, indicating that co-offending not only has a direct effect on notification, but that it also changes the effect of offender characteristics on this decision.